A tool for teaching three‐dimensional dermatomes combined with distribution of cutaneous nerves on the limbs. Issue 4 (18th March 2013) - Kooloos, Jan G.M.; Vorstenbosch, Marc A.T.M.
Abstract : A teaching tool that facilitates student understanding of a three‐dimensional (3D) integration of dermatomes with peripheral cutaneous nerve field distributions is described. This model is inspired by the confusion in novice learners between dermatome maps and nerve field distribution maps. This confusion leads to the misconception that these two distribution maps fully overlap, and may stem from three sources: (1) the differences in dermatome maps in anatomical textbooks, (2) the limited views in the figures of dermatome maps and cutaneous nerve field maps, hampering the acquisition of a 3D picture, and (3) the lack of figures showing both maps together. To clarify this concept, the learning process can be facilitated by transforming the 2D drawings in textbooks to a 3D hands‐on model and by merging the information from the separate maps. Commercially available models were covered with white cotton pantyhose, and borders between dermatomes were marked using the drawings from the students' required study material. Distribution maps of selected peripheral nerves were cut out from color transparencies. Both the model and the cut‐out nerve fields were then at the students' disposal during a laboratory exercise. The students were instructed to affix the transparencies in the right place according to the textbook's figures. This model facilitates integrating the spatial relationships of the two types of nerve distributions. By highlighting the spatial relationship and aiming to provoke student enthusiasm, this model follows the advantages of other low‐fidelity models. Anat Sci Educ 6: 277–280. © 2013 American Association of Anatomists.